PATHOLOGY TEACHING LEARNING METHODS – STUDENTS’ PERCEPTION AND FEEDBACK - Dr. Fauzia Sadiq; Dr. Asad Amin; Taha Tariq; Javeria Ahmed; Azan Ali; Dr. Shazia I Rasa (International Journal of Pharmacy & Integrated Health Sciences, 2023)
Background: Pathology is a key subject at the pre-clinical stage of medical training which needs regular feedback. The clinical years of medical students start from 3rd year MBBS, where importance of pathogenesis of disease is taught that enable the students to appreciate medicine with better conception. Monitoring the teaching and learning methods of the facilitators is necessary for departmental quality improvement.  Objectives: The objective of the present cross-sectional study was to evaluate the student’s feedback in form of questionnaire about pathology teaching followed in the college in Lahore Medical & Dental College from 2021 to Dec 2021. Methodology: 345 students participated in the study and filled a structured pre-validated feedback questionnaire regarding the didactic lecture method of teaching being followed at pathology department Lahore Medical and Dental College. Questionnaire included set of questions on teaching and learning methods. Descriptive statistics were used in the form of frequency distribution and percentages were used to analyze the data. Results: 33.3% students found pathology subject interesting, 47.5% clinically helpful, and 27.5% considered General Pathology to be a difficult subject. Conclusion: Taking feedbacks from the students is one of the accepted and reliable methods of assessment. Majority of the students were satisfied with the present teaching learning method. Introduction of integrated teaching and case based and group-based discussion was favored by majority of the students. Regular feedback will improve our future teaching strategy.